The Reality of The Internship of The Social Work’s Students - Field Study - غفور, ڕزگار مصطفی; فرج, چرۆ محمد (Sulaimani Journal for Humanities, 2019)
The main aim of the present research is to know and identify the reality of internship of the students of the department of social work of college of humanities in the university of sulaimani, and identify statistical difference of the reality of internship according to (sex) and (age) of the students. For that purpose, both the researchers do the descriptive research through using the comprehensive survey method. The research community consists of the students of the fourth stage of the academic year (2017-2018), and their number was (53) students. Both the researchers build the questionnaire contained (32) closed questions. In order to identify the results statistically percentage, mean, weighted mean, one sample T-test and one-way ANOVA had been used. The results showed that the internship of the students of social work not at required level, and requires the solidarity, cooperatively, and coordinately work of formal concerned parties and organizations of Kurdistan regional government to crystallize and succeed the internship of social work.